Opportunities and Challenges of Kurikulum Merdeka Implementation at Sekolah Alam Bukittinggi - Mugni Bustari; Mutia Rosiana Nita Putri (Experimental Student Experiences, 2024)
The author focuses on observational studies at the Sekolah Alam Bukittinggi with a descriptive qualitative approach using literature study research methods. Opportunities found related to the implementation of the Kurikulum Merdeka at Sekolah Alam Bukittinggi are first, the participation of teachers (facilitators) in their Curriculum Workshop activities. Second, the relevance of the era between the Merdeka Curriculum and the Sekolah Alam Bukittinggi’s Special Curriculum, as well as the role of the school principal and the curriculum team in motivating teachers (facilitators) regarding the implementation of the Merdeka Curriculum. Meanwhile, the challenge faced by Sekolah Alam Bukittinggi in implementing the Kurikulum Merdeka is the complexity of the understanding of educational actors in interpreting the implementation of the Kurikulum Merdeka; competence and creativity of teachers (facilitators) in implementing the Kurikulum Merdeka, as well as supervising the implementation of such curriculum. It is hoped that findings regarding the opportunities and challenges of implementing the Kurikulum Merdeka in Sekolah Alam or Nature Schools will become a consideration for schools, teachers, and the government in making appropriate policies so that the objectives of the Kurikulum Merdeka can be achieved effectively. This discovery is also expected to be useful as additional knowledge in further educational research.